2016
DOI: 10.1111/asj.12550
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 impairs mitochondrial functions, activates ROS generation, induces apoptosis and involves Nrf2 signal pathway in primary broiler hepatocytes

Abstract: Aflatoxin B1 (AFB1) is known as a mycotoxin that causes various health problems in animals, but the precise mechanism of AFB1 on mitochondrial functions and apoptosis in primary broiler hepatocytes (PBHs) is not clear. The objective of this study was to investigate the effects of AFB1 on the mitochondrial functions, reactive oxygen species (ROS) generation, apoptosis and nuclear factor erythroid 2-like factor 2 (Nrf2)-related signal pathway in PBHs. Here, the mitochondrial membrane potential (MMP), ROS generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 32 publications
7
83
0
Order By: Relevance
“…In primary broiler hepatocytes, AFB1 caused increased mitochondrial ROS production, decreased mitochondrial membrane potential and induced apoptosis. This was associated with upregulated mRNA expression of Nrf2, but downregulated mRNA expressions of NAD(P)H: quinine oxidoreductase 1, SOD and HO-1 [264]. Similar changes in Nrf2 expression due to the exposure to AFB1 were also observed in broiler cardiomyocytes [265].…”
Section: Mycotoxinssupporting
confidence: 57%
“…In primary broiler hepatocytes, AFB1 caused increased mitochondrial ROS production, decreased mitochondrial membrane potential and induced apoptosis. This was associated with upregulated mRNA expression of Nrf2, but downregulated mRNA expressions of NAD(P)H: quinine oxidoreductase 1, SOD and HO-1 [264]. Similar changes in Nrf2 expression due to the exposure to AFB1 were also observed in broiler cardiomyocytes [265].…”
Section: Mycotoxinssupporting
confidence: 57%
“…Previous studies have reported critical roles of ROS in mycotoxin‐induced cell apoptosis . Here, we further investigated the potential involvement of ROS generation in ENN B1‐associated apoptosis of blastocysts.…”
Section: Resultsmentioning
confidence: 95%
“…A recent study showed that the AFB1 treatment resulted in a significant and concentration-dependent increase in intracellular ROS production, whereas mitochondrial functions such as glutamate/malate and succinate-driven respiration were significantly uncoupled. Those oxidative stress effects activated mitochondrial ROS-dependent signal pathways, which induced apoptosis through the mitochondrial signal pathway [77]. What's more, there are some proteins modulated by AFB1 like CYP1A2, CYP1A5, CYP3A4, TP53, GSMT1, MDM2, CAT, OGG1, IRS1, IRS2, SRC, AKT1, MAPK1, MAPK3, and PDK1.…”
Section: The Metabolism and Toxic Mechanism Of Afb1mentioning
confidence: 99%